Pengaruh Kualitas Pelayanan dan Kualitas Produk Simpan Pinjam Terhadap Kepuasan Anggota KSP CU Bina Karya Sejahtera: The Effect of Service Quality and Savings and Loan Product Quality on Member Satisfaction at KSP CU Bina Karya Sejahtera - Yohana Linda Puspitasari; Murniyati Murniyati (CV Warnak Johanna Nusantara, 2026)
In the world of cooperatives, the most important thing is how satisfied members are with the products and services provided by the cooperative, member satisfaction is used to attract members to use the product. Like a cooperative's obligation to improve the quality of service in order to survive and remain trusted by its members. This study aims to determine the greatest influence of service quality and savings and loan product quality on the satisfaction of KSP CU Bina Karya Sejahtera members. Member satisfaction that influences the service quality and product quality factors. This research method uses a quantitative method using data collection techniques in the form of interviews, questionnaires, and literature studies. The number of respondents taken in this study was 100 respondents who were members of KSP CU Bina Karya Sejahtera. Data analysis used was partial test, simultaneous test, determination coefficient, regression coefficient, and multiple linear regression. The results of the t test showed that each t value of the service quality variable was greater than t table, meaning that service quality had a significant effect on member satisfaction variables. The product quality variable had a t value greater than t table, meaning that product quality had a significant effect on member satisfaction. The results of the F test show that simultaneously the variables of service quality and product quality together have a significant effect on the member satisfaction variable with the results of the analysis. The results of the determination coefficient test show that the factors of service quality and product quality have a significant effect on member satisfaction.